(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Most of the foodborne microbial diseases are linked to foods of animal origin such as milk, meat, and poultry usually have toxic and infectious nature, caused by bacteria, viruses, fungi, parasites and chemical materials that inter to the human body by contaminated food and water. Nowadays, the presence of (MDR) multi-drug resistant pathogens in foods is becoming an increasingly concern about public health in all worldwide due to the excess of antimicrobial drugs in the feed of animal. The MDR pathogens can enter in to the food chain and formation a big danger to both animals and consumers. MDR pathogens causing infections are no care due to their resistance to various type of antibiotics, primarily cephalosporin and carbapenems and to their (ESBL)- extended-spectrum beta-lactamase producing capability. In addition, foods of animal origin and environments related to the food can be likely vehicles and spreading of gene of multi-drug resistance, which accelerates the expansion of global antibiotic resistance. This paper reviews the role of animal origin food as a vehicle for MDR pathogens, stressing the contribution processes of food, environments, and storage conditions in spread and reduction of (AMRs) antimicrobial resistances. Controlling on growth of MDR microorganisms and limiting the transmission/expression of AMR genes in the ecosystems of food could be an effective reducing pathway, putting the focusing efforts on food processes as a part of the AMR in foods. Biological protective cultures are also used as a promising and environmentally friendly technic to reduce the incidence of MDR pathogens, though caution is taken as microbial starters and probiotics can also carry AMR. Finally, applying Whole Genome Sequencing (WGS) and predictive microbiology, within a Risk Assessment framework, is key to get insight into those mechanisms and conditions along the food chain favoring or reducing AMR.